Intergenerational Transmission of Violence from the Family-of-Origin to the Current Family - S Azadi; F Nahidpoor (Iran University of Medical Sciences, 2018)
Abstract Background & Aims: Domestic violence is an annoying and undeniable fact in today's world. This study aimed to investigate the intergenerational transmission of violence from the family-of-origin to the current family in women who referred to the court. Material & Methods: This was a correlational study. The research population comprised of 283 women who referred to the family courts, the forensic medicine center and dispute resolution councils in Shiraz in 2014. Participants were selected by the convenience sampling method and responded to two questionnaires of violence against women and family-of-origin violence. Pearson correlation and regression analysis were used to analyze the data through the SPSS software version 19. Results: Data analysis showed a significant direct correlation between violence in the family-of-origin and violence in the current family (P>0.01), physical violence in the family-of-origin and physical violence in current family (P>0.01), psychological violence in the family-of-origin and psychological violence in current family (P>0.01), economic violence in the family-of-origin and economic violence in current family (P>0.01). In addition, violence in the family-of-origin was a predictor of violence in current family (P<0.01). Conclusion: According to the findings of the research, it can be said that there is a significant direct relationship between violence in the family-of-origin and violence in the current family, and witnessing violence in the family-of-origin is associated with an increased risk of spouse violence victimization in the family of destination